(untitled) (Letras, 2025)
One of the innovative poetic forms developed by Portuguese and Castilian courtly poets of the 15th and 16th centuries were the “poems of mixed forms”. The characteristic of this new form is to present in a single poem, containing a single theme, several other poems that complete or debate or even develop the idea planted in the first poem. In this avant-garde form, for example, the first poem may be “trovas”; after them, the poet can add a “cantiga” and even a “vilancete” —all having the same theme as that presented in the first poem—. There are many of these poems both in Garcia de Resende’s Cancioneiro Geral and in the Cancionero General by Hernando del Castillo. In this brief study, I intend to present the classical, Provençal and Troubadour-Portuguese origins of these poems of mixed forms, in addition to referencing some examples in these two songbooks.